Cutaneous adverse reactions during epidermal growth factor receptor inhibitor therapy - Ragin, Dominika; Basałygo, Magdalena; Nowacka, Katarzyna; Zegarska, Barbara (Dermatology Review/Przegląd Dermatologiczny, 2018)
Epidermal growth factor receptor inhibitors are medications used in the treatment of many neoplasms, including non-small cell lung cancer and colorectal cancer. Because of the expression of epidermal growth factor receptor in the epidermal cells and hair follicles, cutaneous adverse effects occur in many patients during this treatment. The most common dermatological adverse event is development of a papulopustular rash, which is usually accompanied by xerosis and pruritus. Dermatological symptoms observed during treatment with epidermal factor receptor inhibitors also include changes in the nail plate area, changes in the structure and growth of hair, hypersensitivity to ultraviolet radation and mucous membrane changes. These symptoms often significantly impair quality of life and may require a change in oncological therapy. This article summarizes available data about possible methods of preventing or treating cutaneous adverse effects of epidermal growth factor receptor inhibitors.